Clinical findings just after return to play predict hamstring re-injury, but baseline MRI findings do not - De Vos, R.-J.; Reurink, G.; Goudswaard, G.-J.; Moen, M. H.; Weir, A.; Tol, J. L. (British Journal of Sports Medicine, 2014)
Background: Acute hamstring re-injuries are common and hard to predict. The aim of this study was to investigate the association between clinical and imaging findings and the occurrence of hamstring re-injuries.